Transposable element discovery and characterization of LTR-retrotransposon evolutionary lineages in the tropical fruit species Passiflora edulis - Costa, Zirlane Portugal da; Cauz-Santos, Luiz Augusto; Ragagnin, Geovani Tolfo; Van Sluys, Marie-Anne; Dornelas, Marcelo Carnier; Berges, Helene; Varani, Alessandro de Mello [UNESP]; Carneiro Vieira, Maria Lucia (Springer, 2019)
A significant proportion of plant genomes is consists of transposable elements (TEs), especially LTR retrotransposons (LTR-RTs) which are known to drive genome evolution. However, not much information is available on the structure and evolutionary role of TEs in the Passifloraceae family (Malpighiales order). Against this backdrop, we identified, characterized, and inferred the potential genomic impact of the TE repertoire found in the available genomic resources for Passiflora edulis, a tropical fruit species. A total of 250 different TE sequences were identified (96% Class I, and 4% Class II), corresponding to similar to 19% of the P. edulis draft genome. TEs were found preferentially in intergenic spaces (70.4%), but also overlapping genes (30.6%). LTR-RTs accounted for 181 single elements corresponding to similar to 13% of the draft genome. A phylogenetic inference of the reverse transcriptase domain of the LTR-RT revealed association of 37 elements with the Copia superfamily (Angela, Ale, Tork, and Sire) and 128 with the Gypsy (Del, Athila, Reina, CRM, and Galadriel) superfamily, and Del elements were the most frequent. Interestingly, according to insertion time analysis, the majority (95.9%) of the LTR-RTs were recently inserted into the P. edulis genome (<2.0 Mya), and with the exception of the Athila lineage, all LTR-RTs are transcriptionally active. Moreover, functional analyses disclosed that the Angela, Del, CRM and Tork lineages are conserved in wild Passiflora species, supporting the idea of a common expansion of Copia and Gypsy superfamilies. Overall, this is the first study describing the P. edulis TE repertoire, and it also lends weight to the suggestion that LTR-RTs had a recent expansion into the analyzed gene-rich region of the P. edulis genome, possibly along WGD (Whole genome duplication) events, but are under negative selection due to their potential deleterious impact on gene regions.
Keywords: Passiflora; Passion fruit; Genome evolution; Mobile genetic elements; Reverse transcriptase